Een kleurrijke blik op een ondergronds verleden - de Mars, Afra; Van Puyvelde, Judith (Studies over de sociaaleconomische geschiedenis van Limburg, 2024)
Today, the Limburg landscape shows little evidence of its mining past. Existing artwork, on the other hand, regularly references the mining industry. Among the different types of artwork, stained-glass windows are perhaps an unexpected artistic witness of the mining industry and as such constitute a largely overlooked part of mining heritage. This article focuses on these mining windows, which depict the mining industry in various ways. Mining windows have not been the subject of many studies, nor does an overarching catalogue exist. This incited the authors and the Centre for the Social History of Limburg (SHCL) to create the GLiM-project (Stained-glass windows and Dutch mines). The project focuses on compiling an online database of mining windows, starting with those in Dutch Limburg. This article introduces the GLiM-database and zooms in on three case studies: ‘Heilige Barbara’ (1932/1937) by Henri Jonas in Bleijerheide, ‘Eigenschappen van steenkool’ (1938) by Joep Nicolas for DSM, and ‘Het gezonde leven in Limburg’ (1954) by Charles Eyck for the Sanatorium Hornerheide.